2010
DOI: 10.1186/1471-2148-10-211
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and divergence of ADAM family proteins in the Xenopus genome

Abstract: Background: Members of the disintegrin metalloproteinase (ADAM) family play important roles in cellular and developmental processes through their functions as proteases and/or binding partners for other proteins. The amphibian Xenopus has long been used as a model for early vertebrate development, but genome-wide analyses for large gene families were not possible until the recent completion of the X. tropicalis genome sequence and the availability of large scale expression sequence tag (EST) databases. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 83 publications
(114 reference statements)
2
28
0
1
Order By: Relevance
“…Phylogenetic analysis of non-testis-specific human and Xenopus tropicalis ADAMs showed that there are several subfamilies, which remained consistent when other vertebrate ADAMs were analyzed (Wei et al, 2010a). Of these ADAMs, four clades were described.…”
Section: Adamsmentioning
confidence: 64%
See 1 more Smart Citation
“…Phylogenetic analysis of non-testis-specific human and Xenopus tropicalis ADAMs showed that there are several subfamilies, which remained consistent when other vertebrate ADAMs were analyzed (Wei et al, 2010a). Of these ADAMs, four clades were described.…”
Section: Adamsmentioning
confidence: 64%
“…Our phylogenetic and syntenic (gene linkage) analyses suggest that Xenopus ADAM13 is the ortholog of mammalian ADAM33 (Wei et al, 2010a), although the proteins have some key differences. For example, ADAM13 has multiple intracellular SH3-binding motifs and can bind to proteins such as Src and PACSIN2 (Cousin et al, 2000), whereas mouse ADAM33 does not contain any SH3-binding motifs (Gunn et al, 2002).…”
Section: Adams 13/33 and 19mentioning
confidence: 81%
“…A further question is whether these mechanisms are conserved during vertebrate evolution. In mammals, ADAMs 12, 19 and 33 form a subfamily, and our phylogenetic and syntenic analyses suggest that mammalian ADAM33 is the orthologue of frog ADAM13 (Wei et al, 2010a). However, mammalian ADAMs 19 and 33 have nearly equal similarity to Xenopus ADAM13 in protein sequence, raising the possibility that functions of ADAM13 could be shared between ADAMs 19 and 33 in mammals.…”
Section: Discussionmentioning
confidence: 71%
“…X. tropicalis cDNA clones for snail2 (in pCS107; clone ID: Ttba075D05; from Geneservice) and cerberus (in pCS108; clone ID: 7579004; from OpenBiosystems) were identified by bioinformatics and used directly for expression (sequences of all clones were confirmed by DNA sequencing). Cloning of X. tropicalis adam13 has been described previously (Wei et al, 2010a). The coding sequence for ADAM13 was then subcloned into a pCS2+ expression vector modified to append a C-terminal myc 6 -tag.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation